Multicolor fluorescence emission lignin-based carbon dots as well as preparation method and application thereof
By using natural lignin for microwave treatment and surface chemical group regulation, lignin-based carbon dots emitted by multi-color fluorescence are prepared, which solves the problems of high cost of carbon dot precursors and waste of lignin resources in the prior art, and achieves a low-cost and environmentally friendly multi-color fluorescence emission effect, providing new materials for multiple technical fields.
Patent Information
- Application Number
- CN202411579756.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The precursors of existing carbon dots are costly, toxic and have environmental pollution problems. Most of the lignin is burned as industrial waste, causing waste of resources.
Natural lignin is used as raw material, and multi-color fluorescent emission lignin-based carbon dots are prepared through microwave treatment and surface chemical group regulation. The method includes multi-step chemical treatment, such as oxidation, esterification and reduction, to achieve multi-color fluorescence emission by regulating the ratio of electron withdrawing and electron-donating groups on the surface of the carbon dot.
It has achieved low-cost, environmentally friendly and simple preparation of multi-color fluorescent emission lignin-based carbon dots, solved the problems of resource waste and environmental pollution, and provided new material applications for biomedicine, photoelectric conversion and sensing fields.
Smart Images

Figure CN119614188A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lignin-based nanomaterials, and particularly relates to multicolor fluorescent emission lignin-based carbon dots and a preparation method and application thereof. Background Art
[0002] As a new type of zero-dimensional carbon nanomaterial, carbon dots have outstanding advantages such as good water solubility, low toxicity, good biocompatibility, and easy surface modification. With the deepening of the concept of carbon neutrality and the advancement of sustainable development goals, the use of low-carbon and environmentally friendly precursors and simple preparation methods to prepare carbon dots with flexible fluorescence regulation characteristics is crucial for their clean production.
[0003] At present, the precursors of carbon dots are mostly organic synthetic polymers, which are costly, toxic and have environmental pollution problems. Lignin, as a natural aromatic heterocyclic macromolecular polymer, has rich aromatic structures and abundant endogenous heteroatoms in its structure. At present, most lignin is often used as industrial waste for combustion and heat generation, which causes a certain waste of resources. Therefore, it is very necessary to develop a low-carbon, environmentally friendly, simple and multi-color fluorescent emission lignin-based carbon dot preparation method. Summary of the invention
[0004] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a method for preparing multi-color fluorescent emitting lignin-based carbon dots. The present invention uses natural lignin as a raw material and prepares multi-color fluorescent emitting lignin-based carbon dots by flexibly regulating the interaction between its surface chemical groups.
[0005] Another object of the present invention is to provide multicolor fluorescence emitting lignin-based carbon dots prepared by the method.
[0006] Another object of the present invention is to provide an application of the multicolor fluorescence emitting lignin-based carbon dots.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing multicolor fluorescent emitting lignin-based carbon dots comprises the following steps:
[0009] (1) adding lignin and an organic acid to water, stirring and mixing, and then subjecting the mixture to microwave treatment, filtering, taking the filtrate, dialyzing, and freeze-drying to obtain lignin carbon dots (abbreviated as A carbon dots);
[0010] (2) adding the lignin carbon dots and the oxidant obtained in step (1) to water, stirring and reacting at 40-70° C., dialyzing and freeze-drying after the reaction to obtain oxidized lignin-based carbon dots (B carbon dots for short);
[0011] (3) adding the oxidized lignin-based carbon dots obtained in step (2) into water, and then adding an alcohol compound and an acidic catalyst, reacting at 60 to 80° C., and after the reaction is completed, dialyzing and freeze-drying to obtain esterified lignin-based carbon dots (abbreviated as C carbon dots);
[0012] (4) adding the esterified lignin-based carbon dots obtained in step (3) and the reducing agent in a mass ratio of 1:(0.2-0.8) to water, stirring and reacting at 25-50° C., dialyzing and freeze-drying after the reaction to obtain reduced lignin-based carbon dots (abbreviated as D carbon dots);
[0013] (5) Adding the reduced lignin-based carbon dots and the alkaline catalyst obtained in step (4) into water, performing an alkaline hydrolysis reaction at 60-100° C., dialyzing, and freeze-drying after the reaction is completed to obtain multicolor fluorescent emitting lignin-based carbon dots (abbreviated as E carbon dots).
[0014] The lignin described in step (1) includes at least one of alkali lignin, dealkalized lignin, sodium lignin sulfonate and calcium lignin sulfonate.
[0015] The organic acid described in step (1) includes at least one of benzoic acid, formic acid, acetic acid, oxalic acid, lactic acid, citric acid, malic acid, salicylic acid, succinic acid and tartaric acid; preferably at least one of benzoic acid, citric acid, acetic acid and tartaric acid.
[0016] The mass ratio of lignin to organic acid in step (1) is 1:(1-3).
[0017] The amount of water used in step (1) is calculated based on 80-120 mL of water per gram of lignin; preferably, it is calculated based on 100 mL of water per gram of lignin.
[0018] The microwave treatment in step (1) is preferably carried out in a microwave digestion apparatus.
[0019] The microwave treatment conditions in step (1) are: frequency 2000 MHz, power 1000 W, and microwave treatment time 60 to 90 min.
[0020] The dialysis in step (1) is performed using a dialysis bag with a molecular weight cutoff of 500 to 800 Da for 24 to 72 hours; preferably, the dialysis is performed using a dialysis bag with a molecular weight cutoff of 500 Da for 48 hours.
[0021] The dialysate used in the dialysis described in steps (1), (2), (3), (4) and (5) is water.
[0022] The freeze-drying conditions described in steps (1), (2), (3), (4) and (5) are: freeze-drying at -50 to -60°C for 12 to 36 hours; preferably: freeze-drying at -55°C for 24 hours.
[0023] The oxidant described in step (2) includes at least one of sulfuric acid (solution), nitric acid (solution), hydrogen peroxide (or hydrogen peroxide solution), potassium periodate, sodium periodate, potassium permanganate and potassium dichromate.
[0024] The concentration of the sulfuric acid solution is preferably 2 mol / L.
[0025] The concentration of the nitric acid solution is preferably 5 mol / L.
[0026] The mass concentration of the hydrogen peroxide solution is preferably 27%.
[0027] The mass ratio of the lignin carbon dots to the oxidant in step (2) is 1:(1-3); preferably 1:(1-2).
[0028] In steps (2), (3), (4) and (5), the amount of water can be added according to actual needs; in each step, it is preferably calculated based on 80-120 mL of water per gram of lignin; more preferably, it is calculated based on 100 mL of water per gram of lignin.
[0029] The temperature of the stirring reaction in step (2) is preferably 40 to 60°C.
[0030] The stirring reaction time in step (2) is preferably 1 to 3 hours.
[0031] The dialysis described in steps (2), (3), (4) and (5) is performed using a dialysis bag with a molecular weight cutoff of 800 to 1500 Da for 24 to 72 hours; preferably, the dialysis bag with a molecular weight cutoff of 1000 Da is used for 48 hours.
[0032] The alcohol compound described in step (3) includes at least one of tert-butyl alcohol, benzyl alcohol, 2-nitrobenzyl alcohol and 4-bromomethylbenzyl alcohol.
[0033] The mass ratio of the oxidized lignin-based carbon dots to the alcohol compound in step (3) is 1:(1-2) (preferably the alcohol compound is in excess).
[0034] The acidic catalyst described in step (3) includes at least one of sulfuric acid (solution), phosphoric acid (solution), benzenesulfonic acid, 2-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid and acrylic acid cation exchange resin.
[0035] The concentration of the sulfuric acid solution is preferably 2 mol / L.
[0036] The amount of the acidic catalyst added in step (3) is 3% to 7% of the mass of the alcohol compound; preferably 3% to 4% of the mass of the alcohol compound.
[0037] The reaction temperature in step (3) is preferably 60-70°C.
[0038] The reaction time in step (3) is 3 to 6 hours, preferably 4 to 6 hours.
[0039] The reducing agent described in step (4) includes at least one of sodium borohydride, potassium borohydride, vitamin C, sodium sulfide, sodium citrate, hydrazine hydrate and hydroxylamine hydrochloride; preferably at least one of sodium borohydride and vitamin C.
[0040] In step (4), when the mass ratio of the esterified lignin-based carbon dots and the reducing agent is controlled to be 1:0.8, 1:0.6, 1:0.4, and 1:0.2, respectively, single fluorescence emitting lignin-based carbon dots can be obtained, which are blue fluorescence lignin-based carbon dots, green fluorescence lignin-based carbon dots, yellow fluorescence lignin-based carbon dots, and red fluorescence lignin-based carbon dots, respectively; therefore, the present invention can obtain products (powder or solution state) including blue fluorescence, green fluorescence, yellow fluorescence, and red fluorescence lignin-based carbon dots, i.e., multicolor fluorescence emitting carbon dots, by regulating the mass ratio of the esterified lignin-based carbon dots and the reducing agent within the range of 1:(0.2 to 0.8).
[0041] The temperature of the stirring reaction in step (4) is preferably 30 to 50°C.
[0042] The stirring reaction time in step (4) is preferably 12 to 24 hours.
[0043] The alkaline catalyst described in step (5) includes at least one of sodium hydroxide and potassium hydroxide.
[0044] The reduced lignin-based carbon dots and alkaline catalyst 1 described in step (5): (1-2).
[0045] The temperature of the alkaline hydrolysis reaction in step (5) is preferably 70-80°C.
[0046] The alkaline hydrolysis reaction time in step (5) is 3 to 8 hours, preferably 5 to 8 hours.
[0047] A multicolor fluorescence emitting lignin-based carbon dot is prepared by any of the methods described above.
[0048] The multicolor fluorescence emitting lignin-based carbon dots are used in the preparation of carbon nanomaterials and / or biopharmaceuticals.
[0049] The multicolor fluorescent emission lignin-based carbon dots are used in the fields of photoelectric conversion and sensing, ion detection, photoconversion membranes, information encryption or decryption, etc.
[0050] Compared with the prior art, the present invention has the following advantages and effects:
[0051] 1. The natural lignin raw material used in the present invention is low-priced, green, environmentally friendly and renewable.
[0052] 2. The present invention adopts microwave digestion treatment in conjunction with surface chemical group regulation, and the prepared lignin-based carbon dots can achieve blue, green, yellow and red fluorescence emission, which is simple, efficient, low-carbon and environmentally friendly.
[0053] 3. The carbon dot surface oxidation-reduction method used in the present invention accurately controls the relative content of the electron-withdrawing group carboxyl and the electron-donating group hydroxyl, and utilizes the antagonism between the two groups to effectively activate the fluorescence emission migration of the lignin-based carbon dots, thereby achieving its multicolor fluorescence emission.
[0054] 4. The carbon dots prepared in the present invention can be used in many fields such as biomedicine, photoelectric conversion and sensing, ion detection, photoconversion membrane, information encryption and decryption, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is the fluorescence emission diagram of the blue fluorescent lignin-based carbon dots prepared in Example 1 of the present invention at different excitation wavelengths and its CIE coordinate diagram.
[0056] Figure 2 It is the fluorescence emission diagram of the green fluorescent lignin-based carbon dots prepared in Example 2 of the present invention at different excitation wavelengths and its CIE coordinate diagram.
[0057] Figure 3 It is the fluorescence emission graph and CIE coordinate graph of the yellow fluorescent lignin-based carbon dots prepared in Example 3 of the present invention at different excitation wavelengths.
[0058] Figure 4 It is the fluorescence emission diagram of the red fluorescent lignin-based carbon dots prepared in Example 4 of the present invention at different excitation wavelengths and its CIE coordinate diagram.
[0059] Figure 5 It is the fluorescence emission graph and CIE coordinate graph of the blue fluorescent lignin-based carbon dots prepared in Comparative Example 1 of the present invention at different excitation wavelengths.
[0060] Figure 6 It is the fluorescence emission graph and CIE coordinate graph of the blue fluorescent lignin-based carbon dots prepared in Comparative Example 2 of the present invention at different excitation wavelengths. DETAILED DESCRIPTION
[0061] The present invention is further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited thereto. The raw materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods in the following examples where specific conditions are not specified are usually based on conventional conditions.
[0062] The lignin raw materials described in the present invention include alkali lignin, calcium lignin sulfonate, sodium lignin sulfonate and dealkalized lignin, etc. Among the lignin raw materials used in the examples and comparative examples, alkali lignin, sodium lignin sulfonate and calcium lignin sulfonate were purchased from Sinopharm Reagent Co., Ltd.; dealkalized lignin was purchased from MacLean Reagent Co., Ltd.
[0063] The organic acid described in the present invention includes formic acid, benzoic acid, acetic acid, oxalic acid, lactic acid, citric acid, malic acid, salicylic acid, succinic acid, tartaric acid, etc.; the oxidant includes sulfuric acid, nitric acid, hydrogen peroxide, potassium periodate, sodium periodate, potassium permanganate, potassium dichromate, etc.; the acid catalyst includes sulfuric acid, phosphoric acid, benzenesulfonic acid, 2-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, acrylic acid cation exchange resin, etc.; the reducing agent includes sodium borohydride, potassium borohydride, vitamin C, sodium sulfide, sodium citrate, hydrazine hydrate, hydroxylamine hydrochloride, etc.; the basic catalyst includes sodium hydroxide, potassium hydroxide, etc. Wherein, the organic acid, oxidant, acid catalyst, reducing agent, and basic catalyst used in the embodiments and comparative examples are all of analytical grade purity and purchased from Sinopharm Reagent Co., Ltd.
[0064] The alcohol compounds described in the present invention include tert-butyl alcohol, benzyl alcohol, 2-nitrobenzyl alcohol (also known as 2-p-nitrobenzyl alcohol), 4-bromomethylbenzyl alcohol, etc. Among them, the alcohol compounds used in the examples and comparative examples are all of analytical grade purity and purchased from MacLean Reagent Co., Ltd.
[0065] Example 1
[0066] A method for preparing lignin-based carbon dots comprises the following steps:
[0067] (1) 1 g of alkali lignin and 1 g of benzoic acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 60 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0068] (2) adding the A carbon dots obtained in step (1) to 100 mL of water, and then adding 5 mol / L nitric acid solution (the mass ratio of A carbon dots to nitric acid is 1:1), stirring and reacting at 50° C. for 1 h; then dialyzing the reaction solution in water using a 1000 Da dialysis bag for 48 h, and freeze-drying at -55° C. for 24 h to obtain oxidized lignin-based carbon dots (B carbon dots);
[0069] (3) The B carbon dots obtained in step (2) and tert-butyl alcohol (mass ratio of 1:1) were added to 100 mL of water, and a 2 mol / L sulfuric acid solution (the amount of sulfuric acid added was 3% of the mass of tert-butyl alcohol) was added as a catalyst. After reacting at 60° C. for 4 h, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag, and freeze-dried at -55° C. for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0070] (4) adding the C carbon dots obtained in step (3) and sodium borohydride reducing agent (mass ratio of 1:0.8) to 100 mL of water, stirring and reacting at 30° C. for 12 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0071] (5) The D carbon dots obtained in step (4) and sodium hydroxide (mass ratio of 1:1.2) were added to 100 mL of water and reacted at 70°C for 5 h. After the alkaline hydrolysis reaction was completed, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag and freeze-dried at -55°C for 24 h to obtain blue fluorescent lignin-based carbon dots (E carbon dots).
[0072] Example 2
[0073] (1) 1 g of dealkalized lignin and 2 g of citric acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 90 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0074] (2) adding the carbon dots A obtained in step (1) to 100 mL of water, and then adding hydrogen peroxide (the mass ratio of carbon dots A to hydrogen peroxide is 1:2), and stirring the mixture at 40° C. for 3 h; then dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying the mixture at −55° C. for 24 h to obtain oxidized lignin-based carbon dots (carbon dots B);
[0075] (3) adding the B carbon dots obtained in step (2) and 4-bromomethylbenzyl alcohol (mass ratio of 1:1.5) to 100 mL of water, reacting at 70° C. for 4 h under the catalytic action of benzenesulfonic acid (the amount added is 4% of the mass of 4-bromomethylbenzyl alcohol), dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0076] (4) adding the C carbon dots obtained in step (3) and the vitamin C reducing agent (mass ratio of 1:0.6) to 100 mL of water, stirring and reacting at 50° C. for 24 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0077] (5) The D carbon dots obtained in step (4) were added to 100 mL of water, and potassium hydroxide catalyst was added (the mass ratio of D carbon dots to potassium hydroxide was 1:2), and the reaction was carried out at 80°C for 8 h. After the alkaline hydrolysis reaction was completed, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag, and then freeze-dried at -55°C for 24 h to obtain green fluorescent lignin-based carbon dots (E carbon dots).
[0078] Example 3
[0079] (1) 1 g of alkali lignin and 1.5 g of acetic acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 80 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0080] (2) adding the carbon dots A obtained in step (1) to 100 mL of water, then adding potassium permanganate (the mass ratio of potassium permanganate to carbon dots A is 1:1), stirring and reacting at 60° C. for 1 h; dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain oxidized lignin-based carbon dots (carbon dots B);
[0081] (3) adding the B carbon dots obtained in step (2) and 2-p-nitrobenzyl alcohol (mass ratio of 1:1.2) to 100 mL of water, reacting at 70° C. for 4 h under the catalytic action of phosphoric acid (the added amount is 4% of the mass of 2-p-nitrobenzyl alcohol), dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0082] (4) adding the C carbon dots obtained in step (3) and sodium borohydride reducing agent (mass ratio of 1:0.4) to 100 mL of water, stirring and reacting at 40° C. for 18 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0083] (5) The D carbon dots obtained in step (4) were added to 100 mL of water, and then sodium hydroxide catalyst was added (the mass ratio of D carbon dots to sodium hydroxide was 1:1.5), and the reaction was carried out at 70°C for 5 h. After the alkaline hydrolysis reaction was completed, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag, and then freeze-dried at -55°C for 24 h to obtain yellow fluorescent lignin-based carbon dots (E carbon dots).
[0084] Example 4
[0085] (1) 1 g of sodium lignin sulfonate and 3 g of tartaric acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 80 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0086] (2) adding the carbon dots A obtained in step (1) to 100 mL of water, and then adding a 2 mol / L sulfuric acid solution (the mass ratio of carbon dots A to sulfuric acid is 1:1.5), stirring and reacting at 50°C for 3 h; then dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55°C for 24 h to obtain oxidized lignin-based carbon dots (carbon dots B);
[0087] (3) adding the B carbon dots obtained in step (2) and tert-butyl alcohol (mass ratio of 1:2) to 100 mL of water, reacting at 70° C. for 6 h under the catalytic action of 2-aminobenzenesulfonic acid (the amount added is 4% of the mass of tert-butyl alcohol), and then dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0088] (4) adding the C carbon dots obtained in step (3) and the vitamin C reducing agent (mass ratio of 1:0.2) to 100 mL of water, stirring and reacting at 50° C. for 24 h; dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0089] (5) The D carbon dots obtained in step (4) and potassium hydroxide (mass ratio of 1:2) were added to 100 mL of water and reacted at 70°C for 6 h. After the alkaline hydrolysis reaction was completed, a 1000 Da dialysis bag was used to dialyze the reaction solution in water for 48 h. After freeze-drying at -55°C for 24 h, red fluorescent lignin-based carbon dots (E carbon dots) were obtained.
[0090] Comparative Example 1
[0091] In this comparative example, the mass ratio of C carbon dots to reducing agent is 1:0.1, and the rest of the preparation process is the same as that of the above embodiment. The specific preparation method is as follows:
[0092] (1) 1 g of alkali lignin and 1 g of benzoic acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 60 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0093] (2) adding the A carbon dots obtained in step (1) to 100 mL of water, and then adding 5 mol / L nitric acid solution (the mass ratio of A carbon dots to nitric acid is 1:1), stirring and reacting at 50° C. for 1 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain oxidized lignin-based carbon dots (B carbon dots);
[0094] (3) adding the B carbon dots obtained in step (2) and tert-butanol (mass ratio of 1:1) to 100 mL of water, reacting at 60° C. for 4 h under the catalytic action of a 2 mol / L sulfuric acid solution (the amount of sulfuric acid added is 3% of the mass of tert-butanol), dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55° C. for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0095] (4) adding the C carbon dots obtained in step (3) and sodium borohydride reducing agent (mass ratio of 1:0.1) to 100 mL of water, stirring and reacting at 30° C. for 12 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0096] (5) The D carbon dots obtained in step (4) and sodium hydroxide (mass ratio of 1:1.2) were added to 100 mL of water and reacted at 70°C for 5 h. After the alkaline hydrolysis reaction was completed, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag and freeze-dried at -55°C for 24 h to obtain blue fluorescent lignin-based carbon dots (E carbon dots).
[0097] Comparative Example 2
[0098] In this comparative example, the mass ratio of C carbon dots to reducing agent is 1:1, and the rest of the preparation process is the same as that of the above embodiment. The specific preparation method is as follows:
[0099] (1) 1 g of alkali lignin and 1 g of benzoic acid were added to 100 mL of water for stirring and dispersion treatment, and then transferred to a microwave digestion instrument for microwave treatment for 60 min (frequency 2000 MHz, power 1000 W), and then filtered to separate to obtain a filtrate and a filter residue; the filtrate was dialyzed in water for 48 h using a 500 Da dialysis bag, and freeze-dried at -55°C for 24 h to obtain lignin carbon dots (A carbon dots);
[0100] (2) adding the A carbon dots obtained in step (1) to 100 mL of water, and then adding 5 mol / L nitric acid solution (the mass ratio of A carbon dots to nitric acid is 1:1), stirring and reacting at 50° C. for 1 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain oxidized lignin-based carbon dots (B carbon dots);
[0101] (3) adding the B carbon dots obtained in step (2) and tert-butanol (mass ratio of 1:1) to 100 mL of water, adding a 2 mol / L sulfuric acid solution (the amount of sulfuric acid added is 3% of the mass of tert-butanol) as a catalyst, reacting at 60°C for 6 h, dialyzing the reaction solution in water for 48 h using a 1000 Da dialysis bag, and freeze-drying at -55°C for 24 h to obtain esterified lignin-based carbon dots (C carbon dots);
[0102] (4) adding the C carbon dots obtained in step (3) and sodium borohydride reducing agent (mass ratio of 1:1) to 100 mL of water, stirring and reacting at 30° C. for 12 h; using a 1000 Da dialysis bag, dialyzing the reaction solution in water for 48 h, and freeze-drying at -55° C. for 24 h to obtain reduced lignin-based carbon dots (D carbon dots);
[0103] (5) The D carbon dots obtained in step (4) and sodium hydroxide (mass ratio of 1:1.2) were added to 100 mL of water and reacted at 70°C for 6 h. After the alkaline hydrolysis reaction was completed, the reaction solution was dialyzed in water for 48 h using a 1000 Da dialysis bag, and then freeze-dried at -55°C for 24 h to obtain blue fluorescent lignin-based carbon dots (E carbon dots).
[0104] Effect Example
[0105] The fluorescence emission spectra of the fluorescent lignin-based carbon dots prepared in Examples 1 to 4 and Comparative Examples 1 to 2 at different excitation wavelengths were measured using a fluorescence spectrometer and converted into CIE coordinates. Figures 1 to 6 As shown: Figure 1 It is shown that the blue fluorescent lignin-based carbon dots prepared in Example 1 of the present invention have an emission peak at 410 nm at the optimal excitation wavelength of 340 nm, and the CIE coordinates are (0.15, 0.14); Figure 2 It is shown that the emission peak of the green fluorescent lignin-based carbon dots prepared in Example 2 of the present invention is at 495 nm at the optimal excitation wavelength of 360 nm, and the CIE coordinates are (0.26, 0.41); Figure 3 It is shown that the yellow fluorescent lignin-based carbon dots prepared in Example 3 of the present invention have an emission peak at 577 nm at the optimal excitation wavelength of 360 nm, and the CIE coordinates are (0.51, 0.49); Figure 4 It is shown that the red fluorescent lignin-based carbon dots prepared in Example 4 of the present invention have an emission peak at 577nm under the optimal excitation wavelength of 390nm, and the CIE coordinates are (0.71, 0.29). The results show that during the preparation process, when the mass ratio of C carbon dots to reducing agent is 0.2-0.8, the flexible regulation of the fluorescence emission of lignin-based carbon dots from blue, green, yellow to red is achieved, because the antagonism between the electron-withdrawing carboxyl groups and the electron-donating hydroxyl groups on the surface of the carbon dots promotes the red shift of the fluorescence emission of the carbon dots.
[0106] And in Figure 5 In the comparative example 1 (the mass ratio of C carbon dots to reducing agent is 1:0.1), the fluorescent lignin-based carbon dots prepared still emit blue fluorescence at the optimal excitation wavelength of 370 nm, with an emission peak at 421 nm and a CIE coordinate of (0.15, 0.17); Figure 6 In the comparative example 2 (the mass ratio of C carbon dots to reducing agent is 1:1), the emission peak of the fluorescent lignin-based carbon dots prepared at the optimal excitation wavelength of 360 nm is at 432 nm, and the CIE coordinates are (0.14, 0.14), which belongs to the blue area.
[0107] The above results show that when the reduction degree of the carbon dot surface is too low (mass ratio is lower than 1:0.2) or too high (mass ratio is higher than 1:0.8), the surface structure of the carbon dot is single, and a single carboxyl or hydroxyl-related emission state is generated, which makes it difficult to achieve long-wavelength fluorescence emission of the carbon dot, and still presents a single common blue fluorescence. Therefore, within the protection scope of the present invention, a convenient surface chemical structure regulation strategy can be used to utilize the antagonism between the electron-withdrawing carboxyl group and the electron-donating hydroxyl group to achieve multicolor fluorescence emission of a single lignin carbon dot, which can provide technical means for the clean production and development of carbon dots.
[0108] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing multicolor fluorescent emitting lignin-based carbon dots, characterized in that: The steps include: (1) adding lignin and an organic acid to water, stirring and mixing, and then subjecting the mixture to microwave treatment, filtering, taking the filtrate, dialyzing, and freeze-drying to obtain lignin carbon dots; (2) adding the lignin carbon dots and the oxidant obtained in step (1) to water, stirring and reacting at 40 to 70° C., dialyzing and freeze-drying after the reaction to obtain oxidized lignin-based carbon dots; (3) adding the oxidized lignin-based carbon dots obtained in step (2) into water, and then adding an alcohol compound and an acidic catalyst, reacting at 60 to 80° C., and after the reaction is completed, dialyzing and freeze-drying to obtain esterified lignin-based carbon dots; (4) adding the esterified lignin-based carbon dots obtained in step (3) and the reducing agent into water at a mass ratio of 1:0.2-0.8, stirring and reacting at 25-50° C., dialyzing and freeze-drying after the reaction to obtain reduced lignin-based carbon dots; (5) adding the reduced lignin-based carbon dots obtained in step (4) and an alkaline catalyst into water, performing an alkaline hydrolysis reaction at 60 to 100° C., and after the reaction is completed, dialyzing and freeze-drying to obtain multi-color fluorescent emitting lignin-based carbon dots.
2. The method according to claim 1, characterized in that: The lignin in step (1) comprises at least one of alkali lignin, dealkalized lignin, sodium lignin sulfonate and calcium lignin sulfonate; The reducing agent described in step (4) includes at least one of sodium borohydride, potassium borohydride, vitamin C, sodium sulfide, sodium citrate, hydrazine hydrate and hydroxylamine hydrochloride.
3. The method according to claim 1, characterized in that: The organic acid in step (1) comprises at least one of benzoic acid, formic acid, acetic acid, oxalic acid, lactic acid, citric acid, malic acid, salicylic acid, succinic acid and tartaric acid; The oxidant in step (2) comprises at least one of sulfuric acid, nitric acid, hydrogen peroxide, potassium periodate, sodium periodate, potassium permanganate and potassium dichromate; The alcohol compound described in step (3) includes at least one of tert-butyl alcohol, benzyl alcohol, 2-nitrobenzyl alcohol and 4-bromomethylbenzyl alcohol; The acidic catalyst described in step (3) comprises at least one of sulfuric acid, phosphoric acid, benzenesulfonic acid, 2-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid and acrylic acid cation exchange resin; The alkaline catalyst described in step (5) includes at least one of sodium hydroxide and potassium hydroxide.
4. The method according to claim 1, characterized in that: The mass ratio of lignin to organic acid in step (1) is 1:1-3; The mass ratio of the lignin carbon dots to the oxidant in step (2) is 1:1-3; The mass ratio of the oxidized lignin-based carbon dots to the alcohol compound in step (3) is 1:1-2; The amount of the acidic catalyst added in step (3) is 3% to 7% of the mass of the alcohol compound; The reduced lignin-based carbon dots and the alkaline catalyst described in step (5) are in a ratio of 1:1 to 2.
5. The method according to claim 1, characterized in that: The dialysis in step (1) is performed using a dialysis bag with a molecular weight cut-off of 500 to 800 Da for 24 to 72 hours; The dialysis in steps (2), (3), (4) and (5) is performed using a dialysis bag with a molecular weight cut-off of 800 to 1500 Da for 24 to 72 hours; In steps (1), (2), (3), (4) and (5), the dialysate used for dialysis is water.
6. The method according to claim 1, characterized in that: The microwave treatment conditions in step (1) are: frequency 2000 MHz, power 1000 W, and microwave treatment time 60 to 90 min; The freeze-drying conditions described in steps (1), (2), (3), (4) and (5) are: freeze-drying at -50 to -60°C for 12 to 36 hours.
7. The method according to claim 1, characterized in that: The stirring reaction time in step (2) is 1 to 3 hours; The reaction time in step (3) is 3 to 6 hours; The stirring reaction time in step (4) is 12 to 24 hours; The alkaline hydrolysis reaction time in step (5) is 3 to 8 hours.
8. A multicolor fluorescent emitting lignin-based carbon dot, characterized in that: It is prepared by the method according to any one of claims 1 to 7.
9. Use of the multicolor fluorescent emitting lignin-based carbon dots according to claim 8 in the preparation of carbon nanomaterials and / or biopharmaceuticals.
10. Use of the multicolor fluorescent emitting lignin-based carbon dots according to claim 8 in photoelectric conversion and sensing, ion detection, photoconversion membrane, information encryption or decryption.
Citation Information
Patent Citations
Blue-light and green-light lignin carbon quantum dots with high quantum yield as well as preparation method and application thereof
CN113025321A
Preparation method of multicolor fluorescent transparent wood based on carbon quantum dots and transparent wood
CN113459230A
Rapid and simple preparation method of lignin-based carbon quantum dots with high quantum yield
CN113620274A
Preparation method of lignin colorful carbon nanodots as well as product and application of lignin colorful carbon nanodots
CN117327486A
Carbon quantum dot, and method of manufacturing the same
JP2021088477A
Cited By
Lignin-based multicolor fluorescent carbon quantum dot coating as well as preparation method and application thereof
CN122234663A